Preparation, Characterization and Antioxidant Activity of Rice Protein Peptides with Different Enzymatic Hydrolysis Routes - Lingdong LI; Jun CHEN; Lizhen DENG; Qin GENG; Ti LI; Chengmei LIU; Taotao DAI (Shipin gongye ke-ji)
In order to explore the properties differences of rice protein peptides prepared using different enzymatic hydrolysis routes of double enzymes, rice protein was enzymatically hydrolyzed by trypsin (A) and alkaline protease (B) according to different enzymatic hydrolysis routes to obtain five rice protein peptides (A1B1, A1B2, A2B1, A1*B2, A2B1*). The properties of protein peptides including the hydrolysis, basic components, amino acid composition, microstructure, secondary structure, molecular weight distribution, flavor and antioxidant activity in vitro were analyzed. The results indicated that the protein content of A2B1 group was the highest, reaching 90.69% and the peptide content was 72.73%. The hydrolysis degree of five rice protein peptides was greater than 17.60%, the degree of hydrolysis was relatively high, and the microstructure changed from irregular block to sphere. The A1B2 group and A1*B2 group had thicker spheroid walls, A2B1 group and A2B1* group had thinner spheroid walls, and A1B1 group was spheroid fragments. The essential amino acid content of five rice protein peptides was lower than that of rice protein, and the A1B2 group had the highest essential amino acid content. The secondary structure coexisted with a variety of conformations, and the secondary structures of five rice protein peptides were mainly β-turn, and it accounted for 44.62%~47.18%. Most of the enzymatic hydrolysates of five rice protein peptides were polypeptides with low molecular weight, and the polypeptides with molecular weight less than 5 kDa accounted for 92.09%~93.71%. A1B2 samples had the strongest umami and the weakest astringency, and A2B1 samples had the weakest saltiness and bitterness. Compared with A1B1, A1B2 and A1*B2, A2B1 and A2B1* groups had stronger antioxidant activity. Taking together, the quality of A2B1 group was the best based on the evaluation of basic components, peptide content, amino acid composition, flavor and antioxidant activity.